Insights Into Intra-arterial Thrombolysis in the Modern Era of Mechanical Thrombectomy - Castonguay, Alicia C.; Jumaa, Mouhammad A.; Zaidat, Osama O.; Haussen, Diogo C.; Jadhav, Ashutosh; Salahuddin, Hisham; Zaidi, Syed F. (Frontiers in Neurology, 2019)
Background and Purpose: The role of intra-arterial (IA) thrombolysis in modern endovascular therapy is not well-understood. Here, we surveyed neurointerventionalists to understand their current clinical practices and opinions of IA thrombolysis in the new era of mechanical thrombectomy (MT). Method: A 24-question anonymous survey was distributed via email to the members of the Society of Vascular and Interventional Neurology. Results: One hundred and four responses were included in the analysis. Most respondents were interventional neurologists (76.9%) and had ≥5-years in neuro-interventional practice (80.8%). IA thrombolytics are presently used by 60.6%. Aspiration plus stent-retriever was the most common MT approach used with IA-thrombolysis (66.0%). IA-thrombolysis was used in mainly three approaches: (1) treatment of primary distal occlusions, (2) as rescue after proximal occlusion thrombectomy, and (3) or as adjunct therapy to primary MT approach. The most frequent IA-rtPA dose was 3–10 mg, with 1 mg/min infusion rate (56.6%). 84.9% do not have a standardized protocol for administering IA-rtPA. About half (50.9%) believed there should be no time limit for administering IA lytic if there is a favorable imaging profile, while 30.2% indicated ≤6 h. Most respondents (76.5%) would consider using IA-tenecteplase in a trial setting. Only 12.9% felt there was no role for IA thrombolysis in modern endovascular practice. Respondents with ≥10-years' experience were less supportive of the future of IA lytic (98.0 vs. 76.4%, p = 0.006). Conclusion: IA-thrombolysis is currently used in clinical practice; however, there is no clear consensus on best practices or criteria for administration. Further studies are needed to define the role of IA-thrombolysis in the context of MT.